A case-control study of early-life residential exposure to tetrachloroethylene and risks of childhood cancer and birth defects - Jongeun Rhee; Adrian M Michalski; Margaret Gates Kuliszewski; Jamie Musco; Catherine T Adler; Shuai Xie; Melissa C Friesen; Tabassum Insaf; Mark P. Purdue (Environment International)
Background: Residential buildings with a co-located dry-cleaning facility (CL-DC) can have substantially higher indoor tetrachloroethylene concentrations than buildings without a CL-DC. We conducted a case-control study to investigate associations between early-life indoor tetrachloroethylene exposure from CL-DCs and risks of childhood cancers (overall, acute lymphoblastic leukemia) and birth defects. Methods: We linked records between the New York City (NYC) Bureau of Vital Statistics and the New York State Cancer Registry and Birth Defects Registry to identify cases of childhood cancers (n = 5,334) and birth defects (n = 171,553) diagnosed among children born in NYC between 1988 and 2016, and controls without these conditions (n = 596,599). We identified CL-DC exposure by mapping addresses from birth certificates and DC permits involving tetrachloroethylene use to building footprints, and modeled tetrachloroethylene concentrations using measurement data from a survey of NYC CL-DCs. Using unconditional logistic regression, we computed odds ratios (ORs) and 95 % confidence intervals (CIs) relating study endpoints to CL-DC exposure. Findings: Living in a building with a CL-DC at birth was associated with aortic valve stenosis (AVS; OR = 3.1, 95 % CI = 1.6, 5.9), with an exposure–response effect for predicted tetrachloroethylene concentration (≤44 μg/m3: OR = 2.7, 95 % CI = 1.0, 7.4; >44 μg/m3: OR = 3.9, 95 % CI = 1.6, 9.5) and stronger associations for children whose mother was non-White, less than college-educated, or lived at birth in majority non-White or poorer neighborhoods. We observed null findings for other endpoints. Conclusions: In this first-ever case-control study, early-life tetrachloroethylene exposure from CL-DCs in residential buildings was associated with increased AVS risk. These findings warrant further investigation.